Cri(me)s et Hurlements dans Wuthering Heights - Claire Bazin (Cahiers Victoriens et Edouardiens)
If Wuthering Heights is a love story, it is also a story of violence, excess, passion and transgression. Heathcliff is obviously the most violent character, even if, as Terry Eagleton convincingly argues, violence is endemic to the Heights society and his arrival only catalyses a latent aggression. Violence is always already there. The second part of the novel, after the first Catherine’s death, articulates around Heathcliff’s unquenchable thirst for revenge, before he gives up his enterprise once he is convinced that he will join Catherine in a Paradise of their own. I will first analyse the various forms of violence in the novel, then its effects on and within the different characters, before concluding that such excess is self-destructive. The end of the book is placed under the aegis of peace and harmony, which might mean that Emily Brontë has opted for a more traditional Victorian ending. But has she, really?